Non-Intrusive Questions as a Special Type of Non-Canonical Questions. (28th February 2022) - Farkas, Donka F
Abstract: This paper introduces on the scene a new type of non-canonical question, dubbed non-intrusive, exemplified by interrogatives marked by the particle oare in Romanian. It does so by providing an account of the distribution and interpretation of this particle using an updated version of the context components in Fălăuş & Laca (2014), and an elaboration of the general assumptions in Faller (2002) . The intuition the account captures is that by marking an interrogative with oare, the speaker signals that she does not assume that the issue she raises will be resolved in a future state of the conversation. It is further argued that non-intrusive questions are empirically close to but not identical with conjectural questions, discussed most recently in Eckardt (2018), and therefore have to be recognized as a separate category. The predictions and theoretical implications of the account are discussed relative to a general typology of canonical and non-canonical questions.